Implementation of the Exemplary Values of Prophet Muhammad SAW in the Morality of Santri Studying Sirah Nabawiyyah at the Merapi Merbabu Community Pesantren - Dyah Erawati; Surya Hadi Darma; Didih Ahmadiah; Saepul Mukti (Jurnal Inovasi Pendidikan dan Sains, 2025)
This study aims to examine the implementation of the exemplary values of Prophet Muhammad SAW in the moral development of santri through the learning of Sīrah Nabawiyyah, which is integrated into the education system at the Merapi Merbabu Community Pesantren (Islamic Boarding School). This Islamic boarding school adopts Sīrah Nabawiyyah as the foundation for character education based on the “Panca Jiwa” concept, which comprises scholarship, da'wah, volunteerism, community engagement, and entrepreneurship. This study used a qualitative phenomenological approach through observation, interviews, and documentation. The findings indicate that the exemplary values of Prophet Muhammad SAW, such as trustworthiness (amanah), honesty, patience, responsibility, and intelligence, are systematically internalized through the POAC (Planning, Organizing, Actuating, Controlling) approach. Santri are guided through the habituation of moral behavior, involvement in da'wah within the community, and direct modeling from ustadz and musyrif. The success of the program is supported by a curriculum based on Sīrah texts and a synergistic relationship with the surrounding community. Challenges encountered include inconsistency in the moral conduct of santri outside the boarding school environment and the absence of a standardized administrative curriculum. This study provides a significant contribution to the development of a contextual and applicable model of Islamic character education based on exemplary conduct